2016
DOI: 10.1515/mammalia-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of the European hare (Lepus europaeus) in Brazil and new records of occurrence for the Cerrado and Atlantic Forest biomes

Abstract: The introduction of alien species is among the main causes of biodiversity loss. There are many documented cases of introduced mammals having severe impacts on the ecosystem. The European hare (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Amazon forest cottontails and the cottontails found in our study areas represent distinct molecular lineages, suggesting these putative taxa (Silva et al., 2019) may have different fundamental niches and habitat requirements. Despite long‐standing calls (de Faria et al., 2015; Grigera & Rapoport, 1983; Novillo & Ojeda, 2008), our study found little evidence of a negative influence of the non‐native European hares on the native cottontail habitat use, as predicted by the competitive exclusion hypothesis. In contrast to the native cottontail habitat use pattern we found, European hares are less likely to use sites predominantly covered by native forest and more likely to use human‐modified habitats (e.g., sugarcane fields, managed forests, and pastures) in southeastern Brazil (Pasqualotto et al., 2021).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Amazon forest cottontails and the cottontails found in our study areas represent distinct molecular lineages, suggesting these putative taxa (Silva et al., 2019) may have different fundamental niches and habitat requirements. Despite long‐standing calls (de Faria et al., 2015; Grigera & Rapoport, 1983; Novillo & Ojeda, 2008), our study found little evidence of a negative influence of the non‐native European hares on the native cottontail habitat use, as predicted by the competitive exclusion hypothesis. In contrast to the native cottontail habitat use pattern we found, European hares are less likely to use sites predominantly covered by native forest and more likely to use human‐modified habitats (e.g., sugarcane fields, managed forests, and pastures) in southeastern Brazil (Pasqualotto et al., 2021).…”
Section: Discussioncontrasting
confidence: 72%
“…Competition between European hare and Brazilian cottontail has long been suggested given these species' ecological similarities (de Faria et al., 2015; Grigera & Rapoport, 1983; Novillo & Ojeda, 2008). Equivalent to the Brazilian cottontail, European hares are mostly nocturnal (Schai‐Braun et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The animal has unmistakable morphology, especially considering its record in the Caatinga, where there is no documented introduction of the European Brown Hare Lepus europeus (Pallas, 1778). This is an invasive species which has established populations in Southern and Southeastern Brazil (Auricchio and Olmos 1999;Faria et al 2015). Moreover, Sylvilagus has relatively shorter limbs as well as ears proportionally smaller and with lighter colour in relation to Lepus (Feijó and Langguth 2013).…”
mentioning
confidence: 99%